A contribution to the documentation of Siwi (Berber) - Schiattarella, Valentina (AAeO - Afrikanistik-Aegyptologie-Online, 2019)
The aim of this paper is to contribute to the documentation of the Siwi language (Berber, Egypt), through the transcription and translation of an unpublished folktale, recorded by the author in Siwa (Egypt) in 2018. The main stylistic features of the tale are described in the first part of the paper, while grammatical notes on the language are provided in the footnotes, in order to clarify some passages that could otherwise not be easily understood through the transcription, glosses and translation alone.